Systematics and ultrastructure of new and rare chrysophytes from Colorado and Wyoming lakes - Aguiar, Rosane, author; Kugrens, Paul, advisor; Reeves, F. Brent, committee member; Steingraeber, David B., committee member; Chandler, John P., committee member (Colorado State University. Libraries, 2000)
The focus of this study is a description of the Light (LM), Scanning (SEM) and Transmission (TEM) electron microscopic characteristics of nine chrysophytes or goldenbrown algae from Colorado and Wyoming. Phaeaster pascheri var. avesiculosa var. nov. was isolated from Colorado and Wyoming lakes. Cells are compressed in an anterior-posterior indicating a somewhat reniform shape in lateral view. Cells are biflagellate based on TEM but the second flagellum is not evident with either light microscopy or scanning electron microscopy. Cells are covered by oblong non-mineralized scales without ornamentation. Cells have a single, golden-brown lobed chloroplast with a central pyrenoid that has several tubular invaginations of the chloroplast envelope. The nucleus lies near the inner face of the chloroplast and is adjacent to the pyrenoid. This isolate appears similar to Phaeaster pascheri Scherffel, but it lacks the rhizopodial extensions around the flagellar pit, contractile vacuoles and a wide sheath around the long flagellar base. Its systematic position is discussed and a new variety is proposed. A strain of Diacronema vlkianum from Colorado was studied by light and electron microscopy. This is a first report of this alga from the United States. The differences between this isolate from Colorado and a freshwater strain described previously are compared with respect to cell size, flagellar length, and presence of vacuoles. These differences, however, do not merit a separate species designation at this time. The taxonomic position of this golden-brown flagellate was uncertain, and this study corroborates and expands on earlier findings which support its current taxonomic placement. An isolate of Hymenomonas Stein from Colorado is described using light and electron microscopic techniques. Cells usually occurred in a non-motile or palmelloid stage and are covered by non-calcified and calcified scales, the latter known as coccoliths. The coccoliths are distributed in a single layer and each coccolith possesses a basal-plate that is unmineralized. The calcified scales consists of an average of 11 calcium carbonate elements situated between the margin and the raised rim of the baseplate scale. Several layers of non-mineralized scales lie beneath the coccolith layers and are oval and rounded with ornamentations. The pattern of ornamentation on the proximal surface consists of radiating fibrils while the distal surface shows a pattern of concentric fibrils. Four plastids generally are present per cell, each with a bulging pyrenoid that is traversed by paired thylakoids. A single anterior Golgi apparatus often contains developing scales. Flagella and haptonema were not observed in this isolate since the flagellate stage was rare. The ultrastructure of palmelloid cells is compared with cells of H. roseola from Europe. The ultrastructure and systematics of two new freshwater prymnesiophytes are described. An isolate of Prymnesium from a freshwater lake in Wyoming was examined by light and electron microscopy, and this isolate represents the first representative of this genus from a freshwater habitat. Cells vary in morphology, ranging from elongate to subspherical to spherical, with a rounded posterior end and an obliquely truncate anterior end. Two equal or subequal flagella and a short, non-coiling haptonema arise subapically from a groove or depression in the truncate portion of the cell. Two types of organic scales that differ in size, shape, and pattern of ornamentation cover the cell. Chloroplasts vary in number, ranging from one to seven. Each chloroplast has a pyrenoid that protrudes toward the ceil interior and is partially traversed by thylakoids. The second new prymnesiophyte is Chrysochromulina asquamosa sp.nov. and C. asquamosa was collected from five different lakes in Colorado. It is proposed as a new species because it lacks scales. Cells are obovate, spherical, and usually with two chloroplasts, although cells with three to five chloroplasts are common. Each chloroplast has an embedded pyrenoid that is not invaded by thylakoids. The long haptonema (15 pm) and the two subequal flagella are inserted subapically on the concave side of the obovate cell. The flagella lack hairs but both flagella have narrow terminal portions. C. asquamosa resembles C. parva and C. breviturrita, but C. asquamosa differs from both by its smaller cells and lack of scales. Since scale morphology is the most important criterion for delineating Chrysochromulina species, this character provides the basis for proposing a new species. Three colonial chrysophycean flagellates belonging to the genus Uroglena were examined with the electron microscope, and their structure was compared with data other Uroglena species. Scanning electron microscopy (SEM) of U. volvox reveals a colonial structure that is different from any previously described. It is a spherical colony with several hundred cells that are attached by their pointed tails to a. confluent sheet of mucilage, rather than being embedded within a mucilaginous colonial envelope. The spherical colonial mucilage is hollow, and SEM shows that the confluent mucilage consists of a meshwork of fibrils. Cells are obovoid with acutely pointed posterior ends, and a large chrysolaminarin vacuole occupies the posterior one-third of the cell. Each ceil has a single sheet-like, spiral chloroplast with a stigma and a pyrenoid. The pyrenoid is adjacent to the nucleus and projections from the nucleus protrude into the pyrenoid. The stigma is in the anterior end of the chloroplast in a specialized lobe, and is associated with the short flagellum and its flagellar swelling. A descending microtubular root of 11 microtubules begins at the base of the long flagellum and extends around the periphery of the cell, terminating in the cell's posterior. A second Uroglena species is smaller and has up to 32 cells per colony, but an investing colonial envelope or a confluent envelope also is absent. Cells are obovoid with a short pointed end, and the cells are connected to each other by dichotomously branched hollow stalks or tubes. Cells have a single U-shaped chloroplast with a stigma, but lack a pyrenoid. Uroglena articulata is the third colony, and its cells also are connected to each other by sympodially branched stalks but an investing colonial envelope is absent. Cells usually have two chloroplasts with a stigma in one of the chloroplast lobes but pyrenoids are lacking. In addition, an unusual bacterial endosymbiosis was discovered. A rod-shaped bacterium, with its wall intact, grows inside the nuclear envelope of all cells examined. The bacterium did not appear to be pathogenic, but each is a permanent resident of these cells. All three isolates also differ in the fine structure of the flagellar swelling that is associated with the eyespot. The ultrastructure of cells from the colonial chrysophyte Uroglena articulata and the presence of bacteria in the nuclear envelope space are described and discussed- The bacteria appear to be rod-shaped and possess a wall. They are not located near the chloroplasts, and it is postulated that these bacteria either provide some essential nutrient to the alga. The ultrastructure of Ochromonas pleiomorpha sp. nov. is described. Cells are variable in shape, but all possess a single U-shaped chloroplast with lobes of different lengths, and a stigma located in the dorsal lobe. The dorsal lobe usually is shorter than the ventral lobe. A pyrenoid is located toward the inside of the chloroplast and is adjacent to the nucleus on the concave side of the chloroplast. The pyrenoid is invaded by several tubular chloroplast envelope invaginations. A chrysolaminarin vesicle is posterior to the nucleus, and the vesicle membrane is in contact with the posterior portion of the nuclear envelope. The ventral portion of the cell has a concentration of small vesicles that presumably are pre-lysosomal vesicles and/or secondary lysosomes. Light and scanning microscopy revealed that cells may form numerous cytoplasmic extensions (rhizopodia, pseudopodia, filipodia) which may attach cells to a substrate by a posterior extension. Furthermore, the cytoplasmic extensions may be branched. These extensions may form from extrusive vesicles located underneath the plasma membrane. The contents of the vesicles are dark staining and upon discharge the contents become more diffuse. Neither actin microfilaments nor microtubules were observed in these extensions. O. pleiomorpha is an active mixotroph, feeding on diatoms and on its own cells. Diatoms and O. pleiomorpha cells are digested in food vacuoles. After the contents of diatoms are digested in the food vacuoles, empty frustules are released by exocytosis.
Keywords: botany